1.7(-9.7x+6)-5=

Simple and best practice solution for 1.7(-9.7x+6)-5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.7(-9.7x+6)-5= equation:


Simplifying
1.7(-9.7x + 6) + -5 = 0

Reorder the terms:
1.7(6 + -9.7x) + -5 = 0
(6 * 1.7 + -9.7x * 1.7) + -5 = 0
(10.2 + -16.49x) + -5 = 0

Reorder the terms:
10.2 + -5 + -16.49x = 0

Combine like terms: 10.2 + -5 = 5.2
5.2 + -16.49x = 0

Solving
5.2 + -16.49x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5.2' to each side of the equation.
5.2 + -5.2 + -16.49x = 0 + -5.2

Combine like terms: 5.2 + -5.2 = 0.0
0.0 + -16.49x = 0 + -5.2
-16.49x = 0 + -5.2

Combine like terms: 0 + -5.2 = -5.2
-16.49x = -5.2

Divide each side by '-16.49'.
x = 0.3153426319

Simplifying
x = 0.3153426319

See similar equations:

| 0.1x+0.3= | | 6x-5-1+2x-4x=66 | | 7x-8x+x-5x= | | F=(1.8*-5)+32 | | 32x=456 | | 1.5x-3=-1.5x+15 | | 4v-18=6(v-4) | | -5a-2=3(a-6) | | 760-50h=0 | | -9.7(1.7x-5)+6= | | .16x+.8(x-4)=.01(3x-2) | | 3+2x=2(2x+2)-3(x-3) | | 3(2x-6)=4(x+2) | | 2w+2(4x-7)=86 | | 7m+12/8=2m-1/3 | | 4p^2=-9p-2 | | 3x-1+x+x=6.4 | | 3(2x-6)=-4(x-2) | | c^2=33 | | -z-3.2=-22.8+3z | | 0.05(342-x)+0.07x=72 | | 2x+2(x-1)=2x-16+3x | | 3(2x-4)=-4(x-2) | | 16x^2=144-9y^2 | | (10m)/(5m) | | 4x=-2(3x-5) | | z^3-3iz^2-3z+i+1=0 | | 10m/5m | | -9x+12x-10-4x-2x=47 | | 0.3x+0.4=0.9x-1.4 | | 3x^2-8k=16 | | 2y-10x^2+4=0 |

Equations solver categories